TERPENE PRODUCT SEPARATION - Rizki Azaria, Anisya
Terpineol is a hydration product of terpine hydrate from turpentine oil. This hydration reaction yields brownish crude terpineol containing residues of turpentine, terpineol, terpine hydrate, and impurities. Terpineol holds a higher market value (8,160 USD/ton) compared to turpentine (6,630 USD/ton). Based on its boiling point, turpentine acts as a light impurity in crude terpineol. Removing these light impurities can enhance the purity of terpineol. Distillation is chosen for separation because of the significant difference in boiling points among the components in crude terpineol. However, separation at high temperatures leads to the thermal decomposition of compounds in crude terpineol. Thus, vacuum distillation is performed to lower the boiling point of crude terpineol components, aligning with the broader separation region observed in the vapor-liquid equilibrium curve at reduced pressure. This study aims to analyze the optimal operating conditions for separating turpentine from crude terpineol using batch vacuum distillation. The variables investigated include operating pressure and reflux ratio. Operating pressures of 400 mmHg, 450 mmHg, and 500 mmHg are tested, while reflux ratios of 2, 3, and 4 are varied. The experimental procedure comprises three main stages: characterization of crude terpineol, separation of turpentine from crude terpineol using batch vacuum distillation, and characterization of distillation products. Characterization is conducted using Gas Chromatography-Mass Spectrometry (GC-MS) and Gas Chromatography-Flame Ionization Detection (GC-FID). Results show higher turpentine concentration in the distillate as pressure decreases and the reflux ratio increases. Optimal conditions are determined by considering distillate volume, turpentine concentration, and operational costs. Maximizing distillate volume and turpentine concentration while minimizing operational expenses yields optimum conditions at 425.25 mmHg pressure and a reflux ratio of 4. These conditions produce a distillate volume of 92.7 mL, a turpentine concentration of 96.51%, and an operational cost of IDR 24,310.